Virtual Collaboration and E-Democracy During the Pandemic Era: Insights on Digital Engagement, Infrastructure, and Social Dynamics - George Asimakopoulos; Hera Antonopoulou; Ioanna Giannoukou; Antonia Golfi; Ioanna Sataraki; Constantinos Halkiopoulos (Information, 2025)
The COVID-19 pandemic accelerated virtual collaboration, reshaping digital communication, remote work, education, and e-democracy. This study examines the impact of these tools on digital citizen participation through a quantitative cross-sectional survey of n = 1122 participants across diverse demographics. Using stratified purposive sampling, descriptive statistics, correlation analyses, and segmentation by demographic and psychological factors, we analyzed how infrastructure quality, personality traits, and social dynamics influenced virtual engagement. While digital platforms have improved accessibility, findings reveal that they often fail to foster interpersonal trust and democratic deliberation. Statistical analyses demonstrated significant correlations between communication effectiveness and relationship quality (ρ = 0.387, p < 0.001), with distinct patterns emerging across age groups, community sizes, and personality types. Infrastructure disparities significantly impacted participation, particularly in rural areas (χ2 = 70.72, df = 12, p < 0.001, V = 0.145). Recommendations include enhancing digital infrastructure, developing adaptive e-governance platforms, and implementing trust-building mechanisms. Despite the limitations of self-reported data and the cross-sectional design, these insights contribute to building more inclusive digital governance frameworks. Future research should employ longitudinal approaches to explore evolving trends in e-democratic participation.